National German Audit of Diagnosis, Treatment, and Teaching in Secondary Adrenal Insufficiency - Petersenn, Stephan; Honegger, Jürgen; Quinkler, Marcus (Hormone and Metabolic Research, 2017)
Great heterogeneity seems to exist regarding diagnosis, therapy, and teaching of patients with secondary adrenal insufficiency (SAI) across Germany resulting in different diagnosis and treatment strategies. The aim of the work was to present the first national audit on diagnosis, treatment, and patient teaching of SAI reflecting common clinical practice in Germany. A self-designed questionnaire was sent via e-mail to all members of the German Endocrine Society (approx. 120 centers). Returned questionnaires (response rate 38.3%) were checked for duplicity of institutions and analyzed. Diagnostic testing focuses on those patients with relevant risk for adrenal insufficiency. Basal serum cortisol is mostly used as screening test. Short synacthen and CRH tests are the preferred confirmatory tests, however, cut-off values vary due to different assays used. Patients with radiation, second surgery, progressive disease or new symptoms are followed by serial re-testing. Perioperative management and frequency of postoperative re-evaluations differ among centers. Hydrocortisone is the preferred glucocorticoid for replacement therapy, but daily doses vary considerably (10–30 mg/day). Some centers perform hormone measurements for dose adjustment of glucocorticoid replacement therapy whereas others rely on clinical judgement. Patients’ teaching is done in 84% of centers, but only half of the centers include patients’ relatives. Homogeneity exists in patients’ teaching regarding intercurrent illnesses (fever, diarrhoea). Recommendations regarding dose adaptations in situations such as sport-activities, dental-procedures, or coughing are highly variable. This first national audit reveals great heterogeneity among German centers and could improve patients’ care in SAI, for example, by initiating new trials and developing clinical practice guidelines.
Keywords: adrenal insufficiency; pituitary; hydrocortisone; glucocorticoid therapy; patient’s teaching